2022
DOI: 10.1002/ijgo.14299
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of maternal and neonatal death surveillance and response in Cameroon

Abstract: Objective To analyze implementation of maternal and neonatal death surveillance and response (MNDSR) in Cameroon to determine to what extent monitoring objectives are being met and highlight the main obstacles and facilitating factors. Methods Secondary analysis of a cross‐sectional study using a qualitative method and routine data on maternal health. Semistructured interviews were conducted with participants involved in MNDSR at the central, regional, and district levels. Results Notification of maternal deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, the global recommendation to initiate MPDSR programming at tertiary health facilities [ 6 ] may need to be reconsidered in some crisis-affected contexts, where a vast majority of deliveries occur at home and community-based health delivery strategies are in place to compensate for weakened health systems; in these settings, starting with community-based MPDSR approaches may provide more insights on how actors can avert deaths and establish programming where formal health systems are fractured or not functioning [ 15 , 17 19 , 21 , 43 – 47 ]. Some research posits that MPDSR may be underutilized in crisis-affected contexts due to challenges in identifying maternal and perinatal deaths, especially when most occur outside of the formal health system [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the global recommendation to initiate MPDSR programming at tertiary health facilities [ 6 ] may need to be reconsidered in some crisis-affected contexts, where a vast majority of deliveries occur at home and community-based health delivery strategies are in place to compensate for weakened health systems; in these settings, starting with community-based MPDSR approaches may provide more insights on how actors can avert deaths and establish programming where formal health systems are fractured or not functioning [ 15 , 17 19 , 21 , 43 – 47 ]. Some research posits that MPDSR may be underutilized in crisis-affected contexts due to challenges in identifying maternal and perinatal deaths, especially when most occur outside of the formal health system [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Review of maternal death is a key part of MDSR. Maternal death reviews were not carried out routinely and were irregular in most countries [7][8][9][10][11][13][14][15][16] or stopped completely. 12 One healthcare provider noted that financial resources were not available to conduct reviews, which prevented them from happening.…”
Section: Implementing Maternal Death Surveillance and Response In Sub...mentioning
confidence: 99%
“…Notification of maternal death is incorporated into routine health management information systems via integrated disease surveillance and response systems in Benin, 7 Burkina Faso, 8,9 Cameroon, 10 Central African Republic, 11 Chad, 12 Ghana, 13 and Liberia 14 . However, most of the countries continue to underreport maternal and neonatal deaths 12 and many countries do not include neonatal deaths in the notification system 15 .…”
mentioning
confidence: 99%
“…The strategy has become widely established globally, especially since the publication of detailed technical guidance by WHO in 2013 2 . However, notwithstanding the wide global uptake of the intervention, different studies have reported on the inadequate implementation of MDSR in different settings, due to the lack of implementation of the recommendations from maternal death review (MDR) sessions, the absence of verbal autopsy for deaths, the low commitment of districts, 6 the poor availability of reports, incomplete data and missing key information 7 . Among positive factors, planning has been identified as a catalyst for MDSR by previous studies, but the mechanism of its positive influence has not been studied 8,9 …”
Section: Introductionmentioning
confidence: 99%